Manipulating Li2S2/Li2S mixed discharge products of all-solid-state lithium sulfur batteries for improved cycle life - Jung Tae Kim; Adwitiya Rao; Heng-Yong Nie; Yang Hu; Weihan Li; Feipeng Zhao; Sixu Deng; Xiaoge Hao; Jiamin Fu; Jing Luo; Hui Duan; Changhong Wang; et al. (Nature Communications, 2023)
Abstract All-solid-state lithium-sulfur batteries offer a compelling opportunity for next-generation energy storage, due to their high theoretical energy density, low cost, and improved safety. However, their widespread adoption is hindered by an inadequate understanding of their discharge products. Using X-ray absorption spectroscopy and time-of-flight secondary ion mass spectrometry, we reveal that the discharge product of all-solid-state lithium-sulfur batteries is not solely composed of Li2S, but rather consists of a mixture of Li2S and Li2S2. Employing this insight, we propose an integrated strategy that: (1) manipulates the lower cutoff potential to promote a Li2S2-dominant discharge product and (2) incorporates a trace amount of solid-state catalyst (LiI) into the S composite electrode. This approach leads to all-solid-state cells with a Li-In alloy negative electrode that deliver a reversible capacity of 979.6 mAh g−1 for 1500 cycles at 2.0 A g−1 at 25 °C. Our findings provide crucial insights into the discharge products of all-solid-state lithium-sulfur batteries and may offer a feasible approach to enhance their overall performance.